Morphological revision of the genus Aiptasia and the family Aiptasiidae (Cnidaria, Actiniaria, Metridioidea) - Grajales, Alejandro; Rodríguez, Estefanía (Zootaxa, 2014)
Sea anemones of the genus Aiptasia Gosse, 1858 are conspicuous members of shallow-water environments worldwide and serve as a model system for studies of cnidarian-dinoflagellate symbiosis. However, to date there have been no comprehensive analyses investigating the systematics of the group. In addition, previously published phylogenetic studies of sea anemones have shown that the genus is not monophyletic. Herein we revise the genus Aiptasia and the family Aiptasiidae Carlgren, 1924 using newly-collected material. We find that the formerly-named A. pallida (Agassiz in Verrill, 1864) (now Exaiptasia pallida comb. nov.) encompasses a single, widespread species from the tropics and subtropics; we erect a new genus, Exaiptasia gen. nov., for this species primarily based on cnidae, mode of asexual reproduction and symbionts. We also find morphological evidence that supports splitting A. mutabilis into two species: A. couchii (Cocks, 1851) and A. mutabilis. In addition, we find Bellactis Dube, 1983 (formerly placed within Sagartiidae Gosse, 1858) and Laviactis gen. nov. (formerly known Ragactis Andres, 1883, whose familial placement was previously uncertain) belonging within Aiptasiidae. Aiptasiidae is a morphologically homogeneous family whose members (those species in genera Aiptasia, Aiptasiogeton Schmidt, 1972, Bartholomea Duchassaing de Fombressin & Michelotti, 1864, Bellactis, Exaiptasia gen. nov., and Laviactis gen. nov.) are characterized by ectodermal longitudinal muscles in the distal column, rows of cinclides in mid-column, microbasic b-mastigophores in the column, and acontia with basitrichs and microbasic p-amastigophores.